2021
DOI: 10.3390/cells11010093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p53 Protein in the Realization of the Exogenous Heat Shock Protein 70 Anti-Apoptotic Effect during Axotomy

Abstract: The search for effective neuroprotective agents for the treatment of neurotrauma has always been of great interest to researchers around the world. Extracellular heat shock protein 70 (eHsp70) is considered a promising agent to study, as it has been demonstrated to exert a significant neuroprotective activity against various neurodegenerative diseases. We showed that eHsp70 can penetrate neurons and glial cells when added to the incubation medium, and can accumulate in the nuclei of neurons and satellite glial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Demyanenko et al [74] reported that eHSP70 reduces the level of p53 protein and inhibits the pro-apoptotic effect of WR1065 in neurons. This indicates that eHSP70 is involved in regulating p53 activity through the JNK-dependent signaling pathway [74]. The p53 is an important regulator of apoptosis.…”
Section: Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Demyanenko et al [74] reported that eHSP70 reduces the level of p53 protein and inhibits the pro-apoptotic effect of WR1065 in neurons. This indicates that eHSP70 is involved in regulating p53 activity through the JNK-dependent signaling pathway [74]. The p53 is an important regulator of apoptosis.…”
Section: Cell Deathmentioning
confidence: 99%
“…Heat-stimulated HSP70 overexpression is effective in controlling blood sugar levels and suppressing chronic low-grade inflammation in individuals with limited physical activity levels, such as those with severe obesity, muscular dystrophy, people in wheelchairs, and the elderly [62]. Demyanenko et al [74] reported that eHSP70 attenuates apoptosis and necrosis in glial cells, but not in neurons, indicating that eHsp70 also has a neuroprotective effect. Increased eHSP70 expression appears to have little risk of promoting muscle and nerve atrophy [18].…”
Section: Thermal Stimulationmentioning
confidence: 99%
“…[31] Sustained JNK activation promotes apoptosis. [32] eHsp70 reduces apoptosis and necrosis of glial cells, but not neurons.eHsp70 reduces levels of the p53 protein apoptosis promoter (neuroprotective effect). [33] Intranasal injection of recombinant Hsp70 reduced the level of apoptosis in the ischemic penumbra and stimulated axon formation.Exogenous Hsp70 significantly reduced light-induced apoptosis and necrosis of glial cells.…”
Section: Category Finding Referencementioning
confidence: 99%
“…JNK expression is suppressed as HSP72 expression increases; it has also been shown that JNK inhibits mitochondrial respiration and increases the production of ROS to cause apoptosis [41]. JNK activation is an important step in the cellular response to stress; however, prolonged JNK activation can lead to cell damage and cell death [32]. An increase in HSP72 expression due to thermal stimulation may, in turn, reduce the activity of JNK.…”
Section: Apoptosismentioning
confidence: 99%